Bone Scintigraphy and CT Findings in Transverse Process Apophysitis. (July 2016) - Dua, Sumeet G.; Ali, Amjad
Abstract : Abstract: A 14-year-old avid gymnast presented with recent onset of increasing lower thoracic back pain. Clinical examination revealed point tenderness at about T10 level. Focal uptake was seen to the left of the midline on a bone scan ordered to exclude stress fracture. Spine CT when read in conjunction with the bone scan revealed apophysitis of the transverse process. Apophysitis of the posterior elements of the vertebrae is a rare cause of back pain in adolescents.